?SYNTHESIS OF NEW BENZOTHIAZOLE-2-ACRYLIC ACID DERIVATIVES (Biological Sciences - PJSIR, 1995)
Benthothiazole-2-acrylic acid IV reacted with thiourea to give the thiazole derivative V which reacted with different aldehydes to give compounds of the type VI.Also, compound IV reacted with some sulfa drugs and some amines to give amide derivatives of the type VII and IX. respectively. The prepared compounds showed potential antimicrobial activity.